Mimicking of five human senses using nanostructured ZnO single material. (28th September 2018) - Lee, Aram; Choi, Jae-Young; Yu, Hak Ki
Abstract: We demonstrated a single-material multifunctional sensor using ZnO nanorods, which is capable of mimicking the five human senses. A simple method for the growth of ZnO nanorods and their application as a multifunctional sensor was studied. High-density ZnO nanorods were synthesized by the carbothermal transport method on a graphene catalyst. To optimize the sensing mechanisms, we investigated ZnO nanostructure growth under two oxygen flow rates. ZnO nanorods as sensors for smell, light, sound, touch, and taste, the five human senses, showed stable electrical signals under standard ambient conditions.